Simulator investigations of non-maneuverable aircraft reaching high angles of attack in a controlled way - P. L. Sverkanov (Научный вестник МГТУ ГА, 2025)
In-flight experiments are considered the most appropriate means to simplify the development of mathematical models of transport-type aircraft aerodynamic characteristics, which take into account the dynamics of forces and moments arising over a wide range of angles of attack up to the highest ones. This paper is to examine the flight technique to control transport aircraft reaching the angles of attack far beyond their permissible values using on-ground simulation. A mathematical model of transport aircraft which eliminates distortion in aerodynamic characteristics determination arising due to automation in longitudinal axis affecting stability and controllability characteristics is developed for this. To do this, the stabilizer displacement velocity is assumed proportional to manipulator deviation from its neutral position in pitch; in case the control is performed with elevator only, the pilot manually disables this stabilizer displacement. Experiments conducted with PSPK-102 simulator allowed decreasing the rate of deceleration to zero until stall, as well as determination of required values of the deceleration rate assuming there are no restrictions imposed on stabilizer displacement velocity. It is determined that the combined control with elevator and stabilizer increases the range of achievable angles of attack with the use of full elevator pitching up which provides the dynamical reaching the highest angles of attack. It is shown as well that the tendency to stall accompanied by intense lateral motion can be diminished by using yaw stability automation with side-slip angle signal and cross-coupling between ailerons and rudder.